EFFORTS USING LEARNING MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TO IMPROVE STUDENTS ACTIVENESS ON COURSE ASKEB I (PREGNANCY) IN PRODI DIII MIDWIFERY STIKES MINANG PADANG 2015 - Wuri Komalasari Utami Ariyasra (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
In the course Askeb I (Pregnancy) Academic Year 2013/2014 , in which 112 students on subjects Askeb I which has a value of A and B is at least 35 people (31.25%) . This illustrates clearly that 68.75% of the students in the course Askeb I have a level of understanding that is only limited by graduation . The researchers used an alternative model of learning that can improve student learning activities in the course Askeb I (pregnancy) through a cooperative learning model CIRC aimed at improving student learning activeness in Prodi DIII Midwifery STIKes Minang Padang 2015 .This research is a classroom action research (classroom action research) undertaken by researchers directly , which is done by 3 cycles . Each cycle consists of four activities namely : planning, action , observation , and reflection . Samples were students Prodi DIII Midwifery STIKes Minang Padang in 2015 the number of students 11 people . An instruments using documentation , questionnaire , and observation .Based on the results of learning activities of students in the first cycle (56.36%) medium category , in the second cycle (65.45%) medium category , and the third cycle (89.08%) higher category . It can be concluded that the use of cooperative learning model CIRC can improve student learning activities .The researchers suggest to lecturers to use cooperative learning model CIRC one alternative for further learning in other subjects such as Askeb III , Askeb V , Documentation Obstetrics , and Reproductive Health , to improve the learning activities of students and can be submitted as reference and consideration of reference for subsequent studies